Aircraft systems mechanical, electrical, and avionics subsystems integration - Moir, Ian; Seabridge, A. G. (Aerospace series, 2008)
Advances in systems technology continue to ally systems and avionics, with aircraft support and flight systems ever increasingly controlled and monitored by electronics. This updated edition reflects the significant technological and procedural changes that have taken place over the last five years.